Rhipicephalus (Boophilus) Microplus Ticks can Complete their Life Cycle on the Water Buffalo (Bubalus bubalis) - Benitez, Daniel; Cetra, Bibiana; Florin-Christensen, Monica (Journal of Buffalo Science, 2012)
Rhipicephalus (Boophilus) microplus is considered one of the most important ectoparasites of cattle worldwide. Due to the increase in the number of water buffaloes (Bubalus bubalis) in R. microplus-infested areas, this study was designed to determine whether these ruminants are able to sustain the complete tick life cycle. To this aim, a seven-month old water buffalo of the Mediterranean breed and a Holstein bovine of the same age, both tick-naïve, were infested with R. microplus tick larvae, and the parasitic and non-parasitic tick stages were analyzed and compared. The studied parameters include the number of recovered engorged females, the time points at which the first and last engorged females fell to the ground; the pre-oviposition duration, the percentage of hatching and the reproductive efficiency index. No statistically significant differences were found between the buffalo and the bovine in all parameters measured. It was concluded that the water buffalo can act as a suitable reservoir for R. microplus ticks. These results should be taken into account when implementing tick control and eradication campaigns in water buffalo grazing lands.